2018
DOI: 10.1111/jsap.12810
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological frequency of feline hepatobiliary disease in the UK

Abstract: This is the first study to document the histopathological frequency of hepatobiliary diseases in a large cohort of cats in the UK, as well as novel breed and age predispositions. These data may help increase the index of suspicion of a particular disease in the absence of a biopsy-confirmed diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 24 publications
9
30
0
Order By: Relevance
“…Early descriptions of neutrophilic cholangitis/cholangiohepatitis reported it as a syndrome of aged cats,12 whereas lymphocytic cholangitis was typically found in younger cats,13 a similar pattern was observed by Hirose et al 5 Other studies found the opposite distribution, and described lymphocytic cholangitis as a disease of older cats, and neutrophilic cholangitis as one of middle-aged and younger cats 1 4. The current study, similar to Bayton et al ’s4 study, found cats with neutrophilic cholangitis to be younger than those with lymphocytic cholangitis and this warrants further investigation. One confounding factor in this and other studies is the failure to distinguish between acute and chronic neutrophilic cholangitis which Callahan Clark et al 1 described as having significantly different ages of onset.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Early descriptions of neutrophilic cholangitis/cholangiohepatitis reported it as a syndrome of aged cats,12 whereas lymphocytic cholangitis was typically found in younger cats,13 a similar pattern was observed by Hirose et al 5 Other studies found the opposite distribution, and described lymphocytic cholangitis as a disease of older cats, and neutrophilic cholangitis as one of middle-aged and younger cats 1 4. The current study, similar to Bayton et al ’s4 study, found cats with neutrophilic cholangitis to be younger than those with lymphocytic cholangitis and this warrants further investigation. One confounding factor in this and other studies is the failure to distinguish between acute and chronic neutrophilic cholangitis which Callahan Clark et al 1 described as having significantly different ages of onset.…”
Section: Discussionsupporting
confidence: 88%
“…Although reversible hepatocellular injury was reported in a number of cases, hepatic lipidosis was only reported in a minority of individuals. These results are similar to the findings in a population of UK cats where biliary and parenchymal disorders made up the majority of submissions 4. However, in the UK population of cats, neutrophilic cholangitis was the most frequent hepatobiliary disease comprising 20.5 per cent of all cases whereas lymphocytic cholangitis only comprised 6.8 per cent 4.…”
Section: Discussionsupporting
confidence: 87%
“…Primary hepatic neoplasia is estimated to account for 1% to 2.9% of all cancers [15,16]. Biliary carcinomas and HCC have been reported at a frequency of 17% and 27% of all feline hepatic neoplasms [6]. In our collections from the USA and UK over the past 10 years, HCC was the most common hepatic primary epithelial cancer (HCC = 71/132, 54%).…”
Section: Discussionmentioning
confidence: 92%
“…The potential impact of DCH on feline health will be of great interest to the global veterinary community because of the popularity of cats as human companion animals [14]. Chronic hepatitis is apparently uncommon in cats, being reported to occur at a frequency of 2.4% of all feline hepatic biopsies [6]. Primary hepatic neoplasia is estimated to account for 1% to 2.9% of all cancers [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation